HIV/AIDS-Related Knowledge Among Malaysian Young Adults: Findings From a Nationwide Survey - Wong, Li Ping; Chin, Caroline-Kwong Leng; Low, Wah Yun; Jaafar, Nasruddin (Medscape, 2008)
Purpose: HIV/AIDS poses a serious threat to young people, both in Malaysia and throughout the world. A nationwide cross-sectional survey was conducted to assess the knowledge, attitudes, and beliefs about HIV/ AIDS among the Malaysian public. This article reports the findings of knowledge about HIV/AIDS among young adults. Methods: A total of 1075 young adult respondents aged 15-24 years participated in this survey. The response rate was 82.2. Results: The data indicated that HIV/AIDS knowledge among the respondents was moderate, with a mean knowledge score of 20.1 out of 32 points. The great majority had adequate knowledge of the major routes of HIV transmission, but fewer were aware of other modes of transmission, such as tattooing and piercing, sharing personal items, and breast-feeding from an infected mother. The great majority knew that HIV is not transmitted by mosquito bites, sharing meals, casual contact, and using public swimming pools and toilets. Conclusions: Misconceptions about HIV/AIDS exist although generally knowledge on HIV/AIDS transmission and prevention was accurate. Education and intervention programs are needed to increase the level of knowledge and awareness of HIV/AIDS. The findings have important implications for the development of primary HIV/AIDS prevention programs for young adults in Malaysia. Â© 2008 Medscape.